Edukacja przyrodnicza elementem procesu wychowania - Elżbieta Buchcic (Studia Ecologiae et Bioethicae)
Upbringing plays an important role in everyone's life, therefore, the priority of actions undertaken should not only be associated with the educational aspect but also the upbringing aspect. This is due to the rapid development of our civilization, which makes it necessary to engage in constant decision-making and have the ability to distinguish positive and negative values. The aim of the prepared material is to show the important role of Natural Sciences in the educational process as an element of upbringing.